Mediating Effect Of Capital Structure On The Influence Of Liquidity, Profitability, And Asset Growth On Firm Value In Companies Listed In The Lq45 Index During The Period Of 2020-2022 - Jonathan, Robert; Lumbantobing, Rudolf; Tampubolon, Lambok D.R. (MSJ : Majority Science Journal, 2024)
This study aims to examine the capability of capital structure as a mediator in the influence of liquidity, profitability, and asset growth on firm value. In this research, liquidity is proxied by CR and OCFR, profitability by ROA and ROE, and asset growth by CAG and FAG. Capital structure is proxied by DER and DAR, while firm value is proxied by Q Tobin and PER. The research sample consists of 19 companies listed in the LQ45 index during the period 2020-2022. Data analysis was conducted using the PLS 3.0 application, which indicates that liquidity and asset growth have a positive influence on firm value, while capital structure has a negative influence on firm value. Profitability does not have a significant influence on firm value. Additionally, liquidity has a negative influence on capital structure, while profitability and asset growth do not have a significant influence on capital structure. Capital structure can act as a mediator in the influence of liquidity on firm value, but does not act as a mediator in the influence of profitability and asset growth on capital structure.